Through-plane gas permeability of gas diffusion layers and microporous layer: Effects of carbon loading and sintering - Orogbemi, O. M.; Ingham, D. B.; Ismail, M. S.; Hughes, K. J.; Ma, L.; Pourkashanian, M. (Journal of the Energy Institute, 2018)
Knowledge of the absolute permeability for the various porous layers is necessary to obtain accurate profiles for water saturation within the membrane electrode assembly (MEA) in a two-phase model of a polymer electrolyte membrane fuel cell (PEMFC). In this paper, the gas permeability of gas diffusion layers (GDLs) coated with microporous layers (MPLs) of various carbon loadings for two different carbon blacks have been experimentally measured. The permeability of the GDL was found to decrease by at least one order of magnitude after the MPL-coating. Also, the permeability of the MPLs was shown to be lower than that of the carbon substrate by 2–3 orders of magnitude. Further, it was found that the gas permeability of the MPLs changes significantly from one carbon loading to another despite the use of a single weight composition for all the MPLs coated, namely 20% PTFE and 80% carbon black. This signifies the possible inaccuracy in estimating the MPL permeability through employing the cross-section SEM images as they do not resolve the MPL penetration into the carbon substrate. Finally, the MPL sintering was found to slightly decrease the permeability of the GDL.
Keywords: PEMFCs; GDL; Carbon loading; Sintering; Gas permeability